The Tradition of Nyewu Shalawat in Pesantren Miftakhul Jannah, Central Java - Muhamad Mahfudin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This research elaborates the practice of nyewu shalawat (recitation for the praise of the Prophet)) in Pesantren Miftakhul Jannah, Central Java. It focuses on the elaboration on the meaning of the prayers recited throughout the process of running the tradition. As a phenomenological study, it sees the tradition through the perspective of functional theory. It argues that the tradition held by the Pesantren is a sort of living hadith. Not only do the people engage in this tradition have some hadith as the basis, they also regard this tradition as a cult that must not be detached from their lives.